2015
DOI: 10.1534/g3.114.014654
|View full text |Cite
|
Sign up to set email alerts
|

Multiple QTL for Horticultural Traits and Quantitative Resistance toPhytophthora infestansLinked onSolanum habrochaitesChromosome 11

Abstract: Previously, a Phytophthora infestans resistance QTL from Solanum habrochaites chromosome 11 was introgressed into cultivated tomato (S. lycopersicum). Fine mapping of this resistance QTL using near-isogenic lines (NILs) revealed some co-located QTL with undesirable effects on plant size, canopy density, and fruit size traits. Subsequently, higher-resolution mapping with sub-NILs detected multiple P. infestans resistance QTL within this 9.4-cM region of chromosome 11. In our present study, these same sub-NILs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“…This result suggests the possibility of this trait QTL fractionating into multiple QTL if higher‐resolution mapped with a set of sub‐NILs that represent a larger introgressed region beyond marker T0532 (toward the centromere). Fractionation of QTL has been reported for other traits in tomato, including late blight disease resistance, fruit size, maturity, and plant architecture (Johnson et al, 2012; Haggard et al, 2013, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests the possibility of this trait QTL fractionating into multiple QTL if higher‐resolution mapped with a set of sub‐NILs that represent a larger introgressed region beyond marker T0532 (toward the centromere). Fractionation of QTL has been reported for other traits in tomato, including late blight disease resistance, fruit size, maturity, and plant architecture (Johnson et al, 2012; Haggard et al, 2013, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Fractionation of a QTL can occur in higher resolution mapping studies due to multiple QTL of small phenotypic effect that are closely linked but were not detected in initial global mapping studies (Mackay et al, 2009). QTL fractionation has been reported in both tomato and maize (Haggard et al, 2013; Haggard et al, 2015; Johnson et al, 2012; Studer and Doebley, 2011). Larger effect QTL may sometimes fractionate into multiple smaller effect QTL with both positive and negative phenotypic effects (Haggard et al, 2013; Haggard et al, 2015; Mackay et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…QTL fractionation has been reported in both tomato and maize (Haggard et al, 2013; Haggard et al, 2015; Johnson et al, 2012; Studer and Doebley, 2011). Larger effect QTL may sometimes fractionate into multiple smaller effect QTL with both positive and negative phenotypic effects (Haggard et al, 2013; Haggard et al, 2015; Mackay et al, 2009). Alternatively, coincident QTL for different traits may suggest tight linkage and/or pleiotropy (Mackay et al, 2009; Alonso‐Blanco and Méndez‐Vigo, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples are Solanum pimpinellifolium (Thyr, ; Sen et al ., ), Solanum habrochaites (Vulkova & Sotirova, ; Francis et al ., ), S. lycopersicum (Elenkov, ) and Solanum arcanum (Lindhout & Purimahua, ; Vulkova & Sotirova, ). To broaden the genetic variation of cultivated varieties, parts of the genome of wild tomatoes can be introgressed (Haggard et al ., ). Previous studies have shown that the best source of tolerance is S. arcanum LA2157 (van Heusden et al ., ).…”
Section: Introductionmentioning
confidence: 97%